Mediterranean Diet and Metabolic Syndrome - Josipa Radić; Marijana Vučković; Andrej Belančić; Hana Đogaš; Mislav Radić (Diabetology)
Metabolic syndrome (MetS) is a major health issue defined by central obesity and at least two more of the following factors: high triglycerides, low high-density lipoprotein (HDL) cholesterol, high blood pressure, and high fasting glucose. Managing MetS involves lifestyle changes, with the adherence to a Mediterranean diet (MeDi) playing a crucial role. MeDi, emphasizing the consumption of whole grains, fruits, vegetables, legumes, nuts, and olive oil, has been linked to a reduced risk of type 2 diabetes and improved glucoregulation. A randomized controlled trial showed that a low-carb MeDi resulted in a 30% lower relative risk of developing type 2 diabetes compared to a low-fat diet. Additionally, meta-analytic data highlighted a strong inverse relationship between adherence to the MeDi and the incidence of diabetes. Furthermore, the MeDi’s anti-inflammatory properties help manage obesity-related low-grade chronic inflammation, crucial for weight management and the improvement of quality of life. The improvement of lipid profiles, reductions in low-density lipoprotein and total cholesterol, and an increase in HDL cholesterol were also found to be linked to MeDi adherence. However, despite its benefits, adherence to the MeDi varies widely, often being low to moderate in many Mediterranean populations. Improving adherence through physician advice and patient education is crucial for maximizing the MeDi’s potential to prevent and manage diabetes and diabetes-related complications.